2007
DOI: 10.1128/mcb.01967-05
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Regulation of Hematopoiesis by T Cells in BAZF-Deficient Mice

Abstract: The BAZF (BCL-6b) protein is highly similar to the BCL-6 transcriptional repressor. While BCL-6 has been characterized extensively, relatively little is known about the normal function of BAZF. In order to understand the physiological role of BAZF, we created BAZF-deficient mice. Unlike BCL-6-deficient mice, BAZF-deficient mice are healthy and normal in size. However, BAZF-deficient mice have a hematopoietic progenitor phenotype that is almost identical to that of BCL-6-deficient mice. Compared to wild-type mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…These genes have been implicated in vasculogenesis and/or angiogenesis and BAZF/BCL6B and JUNB have also been implicated in hematopoiesis. [30][31][32][33][34] The profiles of these Sox17 targets during early hematopoietic development further support the critical role of SOX17 in the regulation of HE.…”
Section: Discussionmentioning
confidence: 63%
“…These genes have been implicated in vasculogenesis and/or angiogenesis and BAZF/BCL6B and JUNB have also been implicated in hematopoiesis. [30][31][32][33][34] The profiles of these Sox17 targets during early hematopoietic development further support the critical role of SOX17 in the regulation of HE.…”
Section: Discussionmentioning
confidence: 63%
“…It has been reported that BAZF Ϫ/Ϫ mice are viable, healthy, and normal in size. 22,33 Vasculogenesis and angiogenesis abnormalities in BAZF Ϫ/Ϫ mice have not been reported. However, close examination of the retinas of mice with gene disruption of BAZF showed reduction in vascular density and sprouts in the peripheral part of the developing retinal vascular plexus at P5 ( Figure 5A-E, supplemental Figure 6A).…”
Section: Up-regulation Of Bazf Leads To Degradation Of Cbf1 Via Recrumentioning
confidence: 99%
“…Bim is required for the apoptosis of activated T cells following viral infection, which is critical for limiting antiviral immune responses (50). BAZF is required for secondary responses of memory CD8 ϩ T cells (40) and was recently linked to the homeostasis of hematopoietic progenitors (7). Thus, the observed down-regulation of these genes by miR-155 or miR-K12-11 suggests important roles in the regulation of immune responses to infection as well as in targeting apoptosis to regulate cell survival during lymphocyte differentiation.…”
mentioning
confidence: 99%